2019
DOI: 10.5771/0935-9915-2019-2-3-232
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in SMEs: Implications on Competitive PerformanceDate submitted: October 12, 2017Revised version accepted after double blind review: December 15, 2018

Abstract: This study explores the relevance of corporate social responsibility (CSR) in the context of small and medium-sized enterprises (SMEs). The role of CSR in SMEs has so far been scarcely researched, and the relationship between internationalisation and CSR development in SMEs, in particular, could do with the further study. Since it has been found that organisational capabilities and CSR both impact SME performance, we illustrate these relationships and differentiate between the domestic and internationalised SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…In fact, a recent metaanalysis (Chen et al, 2021) demonstrated that effectuation is generally positively related to firm performance, which is especially true for older companies rather than new ventures, which is in line with the empirical findings of the present study, as in our data the average age of SMEs was 29 years. However, the mediation role of responsibility has been found in previous research on SMEs in the relationships between capabilities and competitive performance (Uzhegova et al, 2019), green organizational culture and green product innovation performance (Chang, 2015,) and entrepreneurial orientation and performance (Courrent et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, a recent metaanalysis (Chen et al, 2021) demonstrated that effectuation is generally positively related to firm performance, which is especially true for older companies rather than new ventures, which is in line with the empirical findings of the present study, as in our data the average age of SMEs was 29 years. However, the mediation role of responsibility has been found in previous research on SMEs in the relationships between capabilities and competitive performance (Uzhegova et al, 2019), green organizational culture and green product innovation performance (Chang, 2015,) and entrepreneurial orientation and performance (Courrent et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Int Entrep Manag J (2022). https://doi.org/10.1007/s11365-021-00793-z 6 (Galkina & Chetty, 2015) and SME's business responsibility (Lähdesmäki & Suutari, 2012;Uzhegova et al, 2018Uzhegova et al, , 2019.We collected the empirical data in two phases. First, an initial sample of 1,000 firms listed in the Bisnode Selector database (see www.bisnode.com) was drawn up.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…However, CSR and responsible business practices in SMEs also need further study [5], since SMEs face distinct challenges in their CSR activities [6], especially when compared to larger multinational enterprises [7]. Despite this, to our knowledge, the role of CSR in SMEs has received very little research attention in comparison, and only recently [8] has research on international entrepreneurship started to assess the importance of CSR from the perspective of SMEs. This is a notable omission in the literature since there is recent evidence that sustainability and responsible business practices can be an important competitive advantage for SMEs [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It confirms that SMEs im-plementing EO and CSR can lead them to permanently adopt sustainable business practices and improve their business performance. Uzhegova et al (2019) found CSR to be the mediate factor of the relationship between network competence and competitive performance.…”
Section: Discussionmentioning
confidence: 88%